Space Crisis: Encounter in the Museum Building or Online? - Milena Jokanović (INSAM)
After witnessing a huge turnaround in the wider social context in the previous period, it seems that the question of the future of museums in the digital environment has begun to take on a very optimistic tone full of potential. There is a growing visibility of these heritage institutions on social networks and an increasingly diverse offer of virtual tours, as well as the use of modern virtual and augmented reality technologies in the interpretation and presentation of cultural heritage, while some works of art and collections are created exclusively for cyberspace. Nevertheless, the museum as a meeting place still seems irreplaceable. At a time of isolation, growing loneliness and fears, studies on the emotions of visitors during their stay in the museum in the last few years show that real, physical spaces of the museum encourage constructive attitudes. Encounters with other visitors as well as with the exhibited artifacts especially prove to be important for positive feelings and the need to visit the museum. We will issue these theoretical premises on selected examples and examine whether modern technologies serve as additional tools of promotion and other possible ways of presenting museum content or, oppositely, whether social media and NFT galleries manage to overcome the need for the museum itself as a place of physical encounter.